2017
DOI: 10.1371/journal.pone.0177078
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of repeated ice tests in the evaluation of ptosis in myasthenia gravis

Abstract: Twenty-six patients with ptosis related to Myasthenia gravis (MG) and 38 controls with ptosis other than MG were included. All patients were tested with the ice test 2 times on separate days in the afternoon. The margin reflex distance (MRD) was measured before and immediately after 2-minute application of ice on the eyelids. The ice test was judged positive if there was an improvement of at least 2.0 mm of MRD after the ice test. Among the patients with negative test results, 'equivocal’ was defined by improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…As in previous reports, the ice test is a simple, specific, and relatively sensitive test for the diagnosis of myasthenic ptosis. [ 5 , 6 , 20 ] In addition, Cogan's lid twitch is reported to have a sensitivity of up to 75% and a specificity approaching 99% in MG with ptosis. [ 21 ] The Cogan's lid twitch, in which the ptotic lid briefly elevates excessively after a vertical saccade from a downgaze position.…”
Section: Discussionmentioning
confidence: 99%
“…As in previous reports, the ice test is a simple, specific, and relatively sensitive test for the diagnosis of myasthenic ptosis. [ 5 , 6 , 20 ] In addition, Cogan's lid twitch is reported to have a sensitivity of up to 75% and a specificity approaching 99% in MG with ptosis. [ 21 ] The Cogan's lid twitch, in which the ptotic lid briefly elevates excessively after a vertical saccade from a downgaze position.…”
Section: Discussionmentioning
confidence: 99%
“…While the reliability of the ice test has been confirmed by several studies [5][6][7][16][17][18][19], values for sensitivity and specificity have varied widely. A recent study suggested the ice test has a sensitivity of only 38.5% after a single test, and repeated tests on the same patient giving the same results 61.5% of the time [20]. However, the study noted that the ice test maintained a very high specificity (97.4%) and positive predictive value (90.9%) even after a single application, and that a second application of the test increased its sensitivity to 73.1% [20].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggested the ice test has a sensitivity of only 38.5% after a single test, and repeated tests on the same patient giving the same results 61.5% of the time [20]. However, the study noted that the ice test maintained a very high specificity (97.4%) and positive predictive value (90.9%) even after a single application, and that a second application of the test increased its sensitivity to 73.1% [20]. This suggests that an initial negative ice pack test should ideally be followed by a second application of the test at a later time.…”
Section: Discussionmentioning
confidence: 99%
“…The ice pack test has been demonstrated to be helpful in supporting a diagnosis of OMG in patients with coexisting TED 45,84 . The ice pack test can also help discriminate ptosis due to MG from other causes including TED 85 …”
Section: Clinical Presentationmentioning
confidence: 99%